(untitled) (Journal Of Educational and Psychological Researches, 2015)
The concept of self is considered one of the important dimensions in the human personality, because feeling of self is an important characteristic in this phase from the psychological point of view. The first source which forms the concept of self is the physical image, where the built and appearance of the body is considered among the vital matters which determine the person’s image of himself/herself. The current research aims to: 1) Identify the level of physical self concept at the kindergarten children. 2) Identify the level of psychological self concept at the kindergarten children. 3) Identify the level of social self concept at the kindergarten children. The researcher prepared a scale for physical, psychological and social self-concept which consists of (120) items. The research’s sample consisted of (50) children who were randomly chosen from five kindergartens in Alkarkh side. The kindergartens were randomly chosen and the questionnaire was distributed to the teachers to answer its items. The coincidence and stability were derived from this scale’s items, where the researcher used the T-Test equation for the sample and society and the Pearson correlation coefficient equation in deriving the coincidence and stability and analyzing the results. The results showed that the kindergarten child has a physical self concept and it develops with age and experiences. Children do not have a psychological or social self concept.